Interlinkages between career development, career needs, career satisfaction and career commitment: case study of a military-oriented tertiary educational institution in Malaysia - Azman Ismail,; Nurrul Hayati Adnan,; Abd Hair Awang,; Nazatul Shima Abdul Rani,; Yusof Ismail, (Faculty of Social Sciences and Humanities, UKM,Bangi, 2015)
In organizational contexts, career development programmes refer to how employers design and administer career programmes to tie up employees’ interests and capabilities with organizational opportunities for current and future organizational adjustment to changes. The programmes motivate employees to choose occupations or professions not only to obtain salaries but also to progress in their career paths. This study was conducted to examine the relationship between career development programmes, perceived career needs, career satisfaction and career commitment in a military-oriented tertiary educational institution in Malaysia. A convenience sampling technique was adopted and questionnaires were administered to 200 employees of this institution’s departments/faculties. Semi-structured interviews were also conducted involving four senior HR managers and supporting staff of the institution’s human resource department. The SmartPLS path model analysis was employed to test the research hypotheses and outcomes of the test confirmed that perceived career needs did act as an important mediating variable in the relationship between career programmes, career satisfaction and career commitment in the organization.